Penyusunan Sistem Pengelolaan Persediaan Dan Aset Tetap Berbasis Website Pada Usaha Penyewaan Alat Multimedia Lof Visual - Tangon, Joseph N.; Wangarry, Andreas R.; Syaefudin, Fanesa I. M.; Kesek, Meike N. (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
Efficient and effective management of inventory and fixed assets are two very important aspects in the sustainability of a business. However, in the digital era like today, the management of both aspects which is still manual can be an obstacle in achieving the desired level of efficiency and effectiveness. Lof Visual, as a multimedia equipment rental business, often faces challenges in managing various inventory and assets. Difficulty in conducting inventory and inaccuracy in assessing assets are some of the problems that can affect the accuracy of financial reports. This study aims to produce an efficient and effective website-based inventory and fixed asset management system. The purpose of this study is to implement the preparation of a website-based inventory and fixed asset management system in improving the management owned. The type of research used is qualitative research. The data collection methods used are interviews, observations, literature studies. The results of the study indicate that the system developed successfully meets user needs and can improve the efficiency of inventory and fixed asset management at Lof Visual.